Fresno County Legal Services picnic at Roeding Park - Watkins, Howard K. (1977)
Ysidro Macias, Patrick Sagala, Ruben Lucero, ?, Charles Kahill, back row: ?, Catalina Peralta, Mary Ludy at picnic tables